Scoundrel: how a convicted murderer persuaded the women who loved him, the conservative establishment, and the courts to set him free - Weinman, Sarah (Ecco, an imprint of HarperCollins Publishers, 2022)
"From the author of The Real Lolita and editor of Unspeakable Acts, the astonishing story of a murderer who conned the people around him-including conservative thinker William F. Buckley-into helping set him free"--